Information system for lactation calculation and data collection in dairy sheep - Dimov D.; Angelov J. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
In the light of new realities in sheep breeding in Bulgaria, developments of new breeding programmes for many local breeds are necessary. The production system is described and perspective sheep breeds are indicated. Milk yield and prolificacy appear to be traits with greater economic importance in local breeds -Pleven black head, Stara Zagora, Maritza and some dairy crosses with East Friesian and Awassi breeds. An information system for lactation calculation and data collection of dairy ewes is described. This information system was designed for monitoring the local dairy sheep. Representative data on milk yield and prolificacy have been provided according to the international regulations and standards.
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)